The Effectiveness of Cognitive Behavioral Therapy on Social Phobia Based on Meta-Cognitive Variables - Lak, Zahra; Golzari, Mahmoud; Borj'ali, Ahmad; Sedaghat, Ma'soumeh (Mediterranean Journal of Social Sciences, 2012)
The present research was carried out to determine the effectiveness of group cognitive-behavioral therapy on social phobia ofShahed university students with regard to meta-cognitive beliefs. Being a clinical study, the present research used as sample 30students of Shahed University suffering from social phobia. These students had received top scores on the SPIN social phobia test. Thesample participants were also evaluated using scales of social phobia (SPIN) and meta-cognitive (MCQ30). Being homogenized, theparticipants were divided into experiment and control groups. The experimental group was taught cognitive-behavioral therapy during 20sessions but control group was not included in any educational program. The obtained results were analyzed using descriptive statistics,correlation, and covariance analysis using SPSS. The experimental and control groups were found to be significantly different in terms ofsocial phobia in all three stages: prior therapy, after therapy and 6 weeks later. This implied that cognitive behavioral therapy waseffective in reducing social phobia. Findings indicated that there was a meaningful relationship between meta-cognitive beliefs and thecorresponding effectiveness of cognitive behavioral therapy.